Efficacy Comparison of Various Repair Techniques for Flexor Tendon Injuries: A Systematic Review and Meta-Analysis - Putra, Anak Agung Gde Duta Maha; Karna, Made Bramantya; Asmara, Anak Agung Gde Yuda; Meregawa, Putu Feryawan ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2021)
Background: Flexor tendon injuries are potentially disabling, as flexor tendons are essential to hand function, playing a vital role in all types of grip, including power and fine pinch grips. However, there has been no consensus regarding the most effective repair technique for this pathology.Methods: A systematic search was conducted based on PRISMA guidelines to identify relevant studies through PubMed, Google Scholar, and Cochrane. A total of 9 studies (266 tendons from 108 patients) were included.Results: In a comparison between the Modified Kessler and 4-stranded Cruciate techniques, the Four-stranded Cruciate Suture produces a higher 2 mm gap strength (I2 = 93%, p < 0.00001), higher ultimate strength (I2 = 99%, p = 0.02), and better Functional Outcome as measured using the Strickland Criteria (I2 = 0%, p < 0.0001). In a comparison between the 2-Stranded and the 4-Stranded Kessler technique, the 4-Stranded Kessler technique produces a higher 2 mm gap strength (I2= 98%, p =0.02) and higher ultimate strength (I2= 60%, p <0.00001).Conclusion: The current systematic review and meta-analysis suggests that the 4-stranded cruciate repair technique has better strength and functional outcomes than the modified Kessler, especially in zone II and III injuries. The 4-stranded Kessler is also proven to have better strength compared to the 2-stranded Kessler.